Hi
I am looking at a solution to an math problem but I can't get my head around the last step before the solution.
4p+q-(2p-q)^2
= 4p-4p^2 +q-q^2 +4pq
=4p(1-p)+q(1-q) + 4pq ?how did they get from here to the final answer below.
= 4pq+pq+4pq
thanks in advance for any help.
I am looking at a solution to an math problem but I can't get my head around the last step before the solution.
4p+q-(2p-q)^2
= 4p-4p^2 +q-q^2 +4pq
=4p(1-p)+q(1-q) + 4pq ?how did they get from here to the final answer below.
= 4pq+pq+4pq
thanks in advance for any help.